Efficacy and safety of ruxolitinib in steroid-refractory graft-versus-host disease: A meta-analysis - Fan, Shuang; Huo, Wen-Xuan; Yang, Yang; Shen, Meng-Zhu; Mo, Xiao-Dong (Frontiers in Immunology, 2022)
Ruxolitinib is an important treatment for steroid refractory graft-versus-host disease (SR-GVHD). Therefore, we reported the updated results of a systematic review and meta-analysis of ruxolitinib as treatment for SR-GVHD. In addition, we wanted to compare the efficacy and safety between children and adults with SR-GVHD. Overall response rate (ORR) after ruxolitinib treatment was chosen as the primary end point. Complete response rate (CRR), infection, myelosuppression, and overall survival (OS) were chosen as secondary end points. A total of 37 studies were included in this meta-analysis, and 1,580 patients were enrolled. ORR at any time after ruxolitinib treatment was 0.77 [95% confidence interval (CI): 0.68–0.84] and 0.78 (95% CI: 0.74–0.81), respectively, for SR-aGVHD and SR-cGVHD. CRR at any time after ruxolitinib treatment was 0.49 (95% CI: 0.40–0.57) and 0.15 (95% CI: 0.10–0.23), respectively, for SR-aGVHD and SR-cGVHD. The ORRs at any time after treatment was highest in mouth SR-cGVHD, followed by skin, gut, joints and fascia, liver, eyes, esophagus, and lung SR-cGVHD. The incidence rate of infections after ruxolitinib treatment was 0.61 (95% CI: 0.45–0.76) and 0.47 (95% CI: 0.31–0.63), respectively, for SR-aGVHD and SR-cGVHD. The incidence rates of overall (grades I–IV) and severe (grades III–IV) cytopenia were 53.2% (95% CI: 16.0%–90.4%) and 31.0% (95% CI: 0.0–100.0%), respectively, for SR-aGVHD, and were 28.8% (95% CI:13.0%–44.6%) and 10.4% (95% CI: 0.0–27.9%), respectively, for SR-cGVHD. The probability rate of OS at 6 months after treatment was 63.9% (95% CI: 52.5%–75.2%) for SR-aGVHD. The probability rates of OS at 6 months, 1 year, and 2 years after treatment were 95% (95% CI: 79.5%–100.0%), 78.7% (95% CI: 67.2%–90.1%), and 75.3% (95% CI: 68.0%–82.7%), respectively, for SR-cGVHD. The ORR, CRR, infection events, and myelosuppression were all comparable between children and adults with SR-GVHD. In summary, this study suggests that ruxolitinib is an effective and safe treatment for SR-GVHD, and both children and adults with SR-GVHD could benefit from ruxolitinib treatment.